Winters, Alan y Shahid Yusuf (2007). Dancing with Giants: China, India, and the Global Economy. Washington: The International Bank for Reconstruction and Development/ The World Bank and the Institute of Policy Studies. 272 pp. - Tello Trillo, Cristina Jazmín (2008)
Esta reseña no presenta resumen.